2015
DOI: 10.1158/1055-9965.epi-14-1181
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Related Conditions and Acute Leukemia in Children with Down Syndrome: A Children's Oncology Group Report

Abstract: Background Children with Down syndrome (DS) have unique immune profiles and increased leukemia susceptibility. Methods Mothers of 158 children with DS diagnosed with acute leukemia at 0-19 years in 1997-2002 and 173 children with DS but no leukemia were interviewed. Associations were evaluated via multivariable unconditional logistic regression. Results No associations were detected for asthma, eczema, allergies, or hypothyroidism. Diabetes mellitus associated with leukemia (odds ratio=9.23, 95% confidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
2
2
0
Order By: Relevance
“…The present study found an inverse association between ALL and some reported symptoms of allergic history such as allergic rhinitis/sinusitis and food allergy, which is in line with previous findings from other interview‐based studies showing that ALL cases were generally less prone to allergic symptoms than controls, 10–13,15,35–40 and in a UK study using medical‐record data 14 . However, other studies based on medical records or administrative data did not find this inverse association 16,17 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study found an inverse association between ALL and some reported symptoms of allergic history such as allergic rhinitis/sinusitis and food allergy, which is in line with previous findings from other interview‐based studies showing that ALL cases were generally less prone to allergic symptoms than controls, 10–13,15,35–40 and in a UK study using medical‐record data 14 . However, other studies based on medical records or administrative data did not find this inverse association 16,17 .…”
Section: Discussionsupporting
confidence: 92%
“…When considering a latency period in the ESTELLE study, our results showed an association of the same order of magnitude, whereas in their meta‐analysis including four studies with a latency period between the onset of atopy and leukemia, Linabery et al. had reported a nearly completely attenuated association between atopy/allergy and childhood ALL 36 …”
Section: Discussionsupporting
confidence: 51%
“…In DS children, epidemiological [1, 1418] and pathophysiological [6, 19–22] evidences argue for a higher risk of infectious events, hematological malignancies and autoimmunity. Our work correlates for the first time detailed immunological findings and infectious events in adult patients with DS.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of asthma in children with DS is different and appears not to be caused or related to atopic tendencies; allergic rhinitis is also less common in children with DS. Reasons for this may include T-cell dysfunction or dysregulation, interference with the production of key cytokines on chromosome 21, and reduced expression of certain leukotrienes that may alter leukotriene function and response to montelukast 7–10. The particular pharmacology of montelukast in children with DS remains an area of ongoing study.…”
Section: Commentarymentioning
confidence: 99%